1992
DOI: 10.1152/ajpregu.1992.263.4.r891
|View full text |Cite
|
Sign up to set email alerts
|

Elevated muscle acidity and energy production during exhaustive exercise in humans

Abstract: This study examined the effect of previous intense exercise on energy production during exhaustive exercise. Subjects (n = 6) performed dynamic knee extensor exercise to exhaustion twice (Ex1 and Ex2) separated by 16 min of recovery consisting of 10 min of rest, 3.5 min of very high-intensity intermittent exercise, and a further 2.5 min of rest. This resulted in an elevated muscle lactate concentration of 13.1 mmol/kg wet wt before Ex2. Muscle lactate concentration was the same at end of Ex1 and Ex2, but the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
58
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 0 publications
12
58
0
2
Order By: Relevance
“…The results also offered no evidence that low pH i accelerates muscle fatigue by decreasing glycolysis. Similarly, in humans, glycolysis and glycogenolysis are not inhibited by the pH i decreases occurring in exhaustive exercise (29,30,194), and studies with electrical stimulation in humans have shown that even though glycolysis and glycogenolysis are reduced somewhat when pH i falls from 6.7 to 6.45, significant activity still remains (415).…”
Section: Effects Of Low Ph On the Rate Of Fatiguementioning
confidence: 97%
“…The results also offered no evidence that low pH i accelerates muscle fatigue by decreasing glycolysis. Similarly, in humans, glycolysis and glycogenolysis are not inhibited by the pH i decreases occurring in exhaustive exercise (29,30,194), and studies with electrical stimulation in humans have shown that even though glycolysis and glycogenolysis are reduced somewhat when pH i falls from 6.7 to 6.45, significant activity still remains (415).…”
Section: Effects Of Low Ph On the Rate Of Fatiguementioning
confidence: 97%
“…The concurrent accumulation of potassium in the muscle interstitium (21) has been suggested to be one cause of fatigue during intense exercise in humans (10). This hypothesis is supported by the finding of the same [K ϩ ] v at exhaustion when subjects performed two exhaustive exercise bouts on the same day, even though time to fatigue was different (3,4). Recently, Juel et al (21) studied interstitial potassium concentrations ([K ϩ ] i ) during graded dynamic exercise in human skeletal muscle using the microdialysis technique.…”
mentioning
confidence: 85%
“…In human muscle, a calculation adapted from Newham et al (1995) can be used to estimate the expected value of non-Pi buering capacity to be around 35 slykes (largely due to protein). In the human quadriceps muscle studied by needle biopsy, when the eect of proton consumption by net PCr hydrolysis are taken into account, non-Pi buering capacity is about 40±45 slykes [recalculated from Bangsbo et al (1992a) and Spriet et al (1987a, b) using cell water % 0.66 l á (kg wet) A1 % 3.2 l á (kg dry) A1 (Sahlin 1978;Spriet et al 1987b)]. Estimates of b have also been obtained by magnetic resonance spectroscopy of the human forearm muscle.…”
Section: Possible Errors In the Calculationsmentioning
confidence: 99%
“…Although this depends upon the regulation of glycogenolysis and proton eux, it is substantially constrained by the creatine kinase equilibrium (Kemp et al 1996a) so that under a wide range of conditions the apparent buering capacity is fairly constant. Relative to the true buering capacity, values of 1.4±1.9 can be calculated from published end-exercise values of pH, PCr and lactate concentration (Bangsbo et al 1992a;Chasiotis et al 1987;Spriet et al 1987a, b). Very roughly, this suggests endexercise muscle lactate concentrations of 25, 20, 15, 5, and 1 mmol á l A1 in groups 1±5, respectively.…”
Section: Lactate Euxmentioning
confidence: 99%